Diffusion Characteristics of Particulate Pollutants Across Street Locations - Zhao, Guangming (Scientific Journal of Technology, 2026)
Street canyons, as a key component of the urban built environment, strongly influence the diffusion and retention of particulate pollutants due to their complex airflow structures. To investigate the diffusion mechanisms of particulate matter released from different locations within street canyons, a two-dimensional idealized canyon model without vegetation was employed. A steady-state flow field was simulated using computational fluid dynamics (CFD), and a Lagrangian particle-tracking approach was applied to analyze particle trajectories and transport behaviors at different spatial positions. Results indicate the formation of a stable primary vortex within the canyon. The central region, characterized by low wind speeds and recirculating streamlines, significantly inhibits particle dispersion, whereas the upper canyon and free-flow regions promote rapid particle removal due to higher wind velocities. Particle release location plays a critical role in diffusion efficiency: particles released near the upper region or close to the free-flow boundary disperse rapidly when their initial momentum aligns with the main flow direction; particles in the vortex core are prone to long-term trapping; and particles near the ground can gradually rise due to boundary layer disturbances but exhibit prolonged residence times. Additionally, the alignment between particle initial velocity and local flow structure significantly affects their ability to escape vortex constraints. These findings highlight the sensitivity of particulate dispersion to spatial location and flow structures within street canyons, providing a theoretical basis for optimizing urban ventilation and pollution control strategies.